Skinning toads is innate behaviour in otter (Lutra lutra) cubs. Issue 4 (1st October 2016) - Morales, J.; Ruiz-Olmo, J.; Lizana, M.; Gutiérrez, J.
Abstract : An experiment was performed with two subadult otters ( Lutra lutra ) born in captivity that had never seen or eaten amphibians, in which they were fed a new prey with toxic substances in its skin, the Iberian common toad ( Bufo spinosus ). It was observed that the otters recognised a poisonous amphibian that they had never come into contact with before as a potential prey in the absence of fish, which had previously been their only diet. As from the first test, and as described for wild otters in the literature, they consumed the toads following a learning process that consisted of ventral slicing and skinning in order to avoid contact with the dermal secretions, especially on the head and back, that toads use as a defensive mechanism. We observed the skill of the otters when handling the prey with regards to both killing them and eating them; the otters also immersed their prey in the water of their pond to remove the toxic substances emanating from the toads' skins. The amount of remains left after the attack was gradually reduced over a period of 16 test experiments. No differences between the skins rejected in the experimental conditions and those found in nature were detected, the otter mainly eating the back legs and taking special care to reject the head, the back and viscera (especially the ovaries in the case of pregnant females). When they had brown trout together with toads in the same biomass, they neither attacked nor consumed the latter.